A2.22 Influence of TNF on the proteome of rheumatoid arthritis synovial fibroblasts. (13th February 2015) - Ossipova, E; Wähämaa, H; Klareskog, L; Catrina, AI; Jakobsson, PJ
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a chronic autoimmune systemic disorder that affects primarily the joints and leads to their destruction. Rheumatoid arthritis synovial fibroblasts (RASFs) localised in the RA synovium play a crucial role in the destructions of joints by production of pro-inflammatory cytokines, matrix-degrading enzymes or via production of matrix metalloproteinases (MMPs). Activated leukocytes or adipocytes secrete Tumour Necrosis Factor (TNF), which in turn stimulates RASFs resulting in production of MMPs, maintenance of inflammation, and induction of osteoclastogenesis. For better understanding on how TNF contributes to RASFs stimulation and to reveal pathways activated by TNF in RASFs, we investigate the effect of TNF-alpha on the proteome of human RASFs obtained from synovial tissues of patients with RA. Materials and Methods: Expanded in cell culture, RASFs (passages 5 and 7) obtained from two CCP- donors, were stimulated with TNF (10 ng/ml, 24 h). Cells were harvested and lysed in buffer containing SDS. Quantitative proteome analysis utilising iTRAQ (Isobaric Tagging for Relative and Absolute Quantification) - labelling was employed to the TNF treated and untreated cells in order to detect gene expression at the protein level. Pathway analysis was performed by using Ingenuity Systems Pathway Analysis (IPA) program. Results: Out of 1028 profiled proteins, 14 proteins exhibited elevated expression and 28 proteins showed reduced expression upon stimulation with TNF-alpha. The following canonical pathways (top 5) were activated: EIF2 Signalling, Regulation of eIF4 and p70S6K Signalling, mTOR Signalling, Remodelling of Epithelial Adherens Junctions and Protein Ubiquitination Pathway. IPA analysis showed that TNF-alpha increased cell-to-cell signalling and interaction and tissue development by increasing attachment of cells, promotion of cell death of connective tissue cells, induction of reactive oxygen species, increased apoptosis and decreased degradation of oxygen peroxide. Conclusions: Quantitative proteomic analysis of RASFs stimulated with TNF-alpha revealed upregulation of several genes involved in inflammatory processes in RA and bone destruction as well as activation of several pathways, which play an important role in protein folding and osteoclastgenesis.